Effect of Culture Conditions on Production Laccase from Trametes versicolor and Partial Purification Extracellular Enzyme - Doan, Chi Cuong; Bui, Duc Thang; Dang, Minh Nhat; Vo, Chau Tuan; Pham, Thi Diem; Nguyen, Thi Bich Hang (Hue University Journal of Science: Natural Science, 2025)
Laccase is a multicopper oxidase enzyme which oxidizes a wide range of substrates, including phenols, ketones, phosphates, ascorbate, amines, and lignin. This study was conducted to evaluate the effects of medium composition, cultivation time, and culture method on laccase production by Trametes versicolor. The results showed that the optimal medium for laccase production consisted of potato extract, glucose, KH₂PO₄, MgSO₄, NH₄⁺, Cu²⁺, and ABTS. Under these conditions, laccase activity reached 2.858 U/mL after 8 days of cultivation. Additionally, the study investigated the effects of different precipitation agents on the efficiency of laccase purification from the culture broth. The ratios of enzyme solution to organic solvents (ethanol, acetone) varied from 1:1 to 1:5 (v/v), and the saturation level of ammonium sulfate ranged from 40% to 80%. The results indicated that ethanol was the most effective precipitating agent, with the highest laccase yield obtained at a ratio of enzyme to ethanol of 1:3 (v/v) and a treatment time of 45 minutes. The molecular weight of the purified laccase was approximately 100 kDa as determined by SDS-PAGE analysis. These findings highlight the potential of T. versicolor culture broth as a source for laccase enzyme production, supporting its application in industrial bioprocesses such as bioremediation, food processing, and the development of sustainable biotechnology solutions.